Existence of Strong Solutions for Nonlinear Systems of PDEs Arising in Convective Flow - Khaled Bouazzaoui; Mohammed Aiboudi; Sameh Elsayed Ahmed (International Journal of Differential Equations)
In this paper, we will study the existence of strong solutions for a nonlinear system of partial differential equations arising in convective flow, modeling a phenomenon of mixed convection created by a heated and diving plate in a porous medium saturated with a fluid. The main tools are Schäfer’s fixed-point theorem, the Fredholm alternative, and some theorems on second-order elliptic operators.